FUNCTIONAL OUTCOME OF NECK OF FEMUR FRACTURE IN ELDERLY PATIENTS MANAGED WITH BIPOLAR HEMIARTHROPLASTY V/S TOTAL HIP REPLACEMENT - KUMAR, ANKUSH; REHNCY, JAGDEEP SINGH; MEHTA, HARRY; SINGH, JASKIRAT; BAKSHI, AMANDEEP SINGH; SAHNI, GIRISH (International Journal of Current Pharmaceutical Research, 2025)
Objective: Femoral neck fractures (FNFs) pose a significant public health challenge, particularly as the global population ages, with incidence rates doubling every decade after age 50. Mortality rates range from 3-10% within 30 days and nearly 30% within a year post-injury, with long-term consequences including the need for extended nursing care in 25% of patients and mobility challenges for nearly 50%. The majority of FNFs are displaced, especially in elderly females, necessitating diverse treatment strategies. Current management options include fracture reduction, bipolar hemiarthroplasty, and total hip replacement (THR), with emerging evidence indicating that THR may offer superior functional outcomes. To evaluate and compare the functional outcomes of displaced FNFs in active elderly patients treated with either bipolar hemiarthroplasty or THR, providing insights into optimal orthopedic management. Methods: This prospective study at Government Medical College, Patiala, assessed 30 elderly patients (aged over 60) with displaced femoral neck fractures (Garden types 3 and 4). Participants were randomly assigned to two treatment groups: Group 1 received bipolar hemiarthroplasty, and Group 2 underwent total hip replacement (THR). All patients provided informed consent, and ethical approval was obtained. The posterior-lateral approach was used for surgical access, followed by a standardized postoperative protocol involving intravenous antibiotics, early mobilization, and follow-up assessments at 2 w, 1 mo, 3 mo, and 6 mo, with functional outcomes evaluated using the Modified Harris Hip Score. Results: In this study, the mean age was 68.67±7.36 y in Group I and 65.97±6.05 y in Group II, with no significant age or gender differences between groups. Operative time was significantly shorter in Group I (79.67±19.99 min) compared to Group II (108.16±24.65 min, p = 0.0410). Intraoperative blood loss was significantly higher in Group II (682.67±142.80 ml) than in Group I (428.33±114.98 ml, p<0.0001). Functional outcomes, measured by the Harris Hip Score, showed significant improvement in Group II at all follow-up intervals (2 w, 1 mo, 3 mo, and 6 mo) compared to Group I (p<0.00001). These findings suggest that THR may lead to better functional recovery than PHR in elderly patients with displaced femoral neck fractures. Conclusion: This study underscores notable differences in clinical outcomes between bipolar hemiarthroplasty (PHR) and total hip replacement (THR) for femoral neck fractures. Patients who underwent THR experienced longer surgical durations, increased intraoperative blood loss, and better functional outcomes, as assessed by the Harris Hip Score, at multiple postoperative follow-up points.